Iowa RBA, January 20, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for January 20, 1997. Highlights of the update include sightings of an unusually large number of Snow Bunting flocks as well as a Pinyon Jay, an Evening Grosbeak, and a Prairie Falcon. Also of note were observations of Red Crossbills, a Common Redpoll, Snowy Owls, and a Long-tailed Duck. Also included are handwritten notes for the next week's update with sightings of a Common Loon and eight species of waterfowl. Epson - sheet feed/flatbed